PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS V SDN. 020 BAGAN JAWA BAGANSIAPIAPI - Sarah Sarah; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The learning approach greatly affect the level of student learning outcomes. In class V SDN 020 Bagan Jawa Bagansiapiapi district. Rokan Hilir in science subjects, so we need an approach to learning that can help students in improving learning outcomes, one of which is to apply the approach of Contextual Teaching And Learning (CTL) in the learning process. This research aims to improve student learning outcomes and help siawa SDN 020 Bagan Jawa Bagansiapiapi district. Rokan Hilir in understanding the material. This research is a classroom action research conducted in the second cycle, which consists of planning, action, observation and reflection. The data obtained in this study include student learning outcomes derived from the provision of test at the end of the cycle, the ability of teachers in the management of lessons learned from observation sheet activities of teacher, student activities taken from student activity observation sheet. The number of students in this study were 11 students. Student learning outcomes in the first cycle students gain an average value of 72.36 with the presentation of classical absorption of 61.92% and 81.82% classical completeness, the observation of teachers 83.33% and 90.91% on the observation of students increased in the second cycle with an average value of 83.82% with a presentation of classical absorption 82.69% and 100% classical completeness, the observation of teachers 95.85% and 97.73% on the observation of students, it can be concluded that the application of the approach can CTL improve the learning outcomes of students of class V SDN 020 Chart Bagansiapiapi Java district. Rohil, because CTL learning model can provide convenience as problem solving, and social Agents Of Change Of Control in learning.Key word : Outcome learning IPA, Contextual Teacing and learning